Linguistic Intelligence and Sentence Structure Mastery towards Students Writing Skill in Recount - ulfa wulan agustina (Universitas KH. A. Wahab Hasbullah, 2018)
This research is a kind of survey and aims to find out and analyze empirically the effects of linguistic inteligenceand sentence structue towards student’s writing skill in recount. The observed population of this research is students of private junior high schools in Depok West Java. The sample was gained through simple random sampling, which means that the researcher mixed the subjects in the population so that they will be considerably the same. This research has 3 variables which are divided into 2 independent variables (linguistic inteligence and sentence structure) and 1 dependent variable (writing skill in recount). The collection of the data is done by questionnaire and written tests for both independent and dependent variables. The gained data was then analyzed by using correlation technique and multiple regressions. Previously, the prerequisite tests before examining the regression test must be accomplished, such as normality test and linearity test. The result of this research is: 1) There are any significant effects of linguistic inteligence and sentence structue altogether towards student’s reading comprehension and it is proved by Fo = 13,014 and Sig.=0.001< 0.05) There is a significant effect of linguistic inteligence towards student’s writing skill in recount and it is proved by to = 3,378 and Sig.=0.000 < 0.05) There , , is a significant effect of sentence structure towards student’s writing skill in recount and it is proved by to = 2,577 and Sig.=0.012< 0.05. It means that the student’s writing skill in recount is strongly influenced by linguistic inteligence and sentence structureof his/her own.